Design and Development of Fuzzy Discretization and Random Forest Framework (FDRFF) for Continuous Data in Decision Making - HISHAMUDDIN, MUHAMMAD NUR FIKRI (2021)
The research aims in improving the classification accuracy of tree-based classifier to accommodate continuous data